An Unusual Presentation of Prostate Carcinoma - Sadasivan, Greeshma; Arul, R; Prabaharan, A (Indian Journal of Medical and Paediatric Oncology, 2018)
Prostate carcinoma is the second most common cancer among men worldwide. Although prostate carcinoma is common, its presentation resembling retroperitoneal fibrosis is uncommon. We report a patient with prostate carcinoma mimicking retroperitoneal fibrosis. An elderly male presenting in a volume overload state with features of obstructive uropathy was diagnosed as a case of prostate carcinoma. Magnetic resonance imaging was suggestive of retroperitoneal fibrosis. The presentation of prostate carcinoma as retroperitoneal fibrosis is rare.
Keywords: Obstructive uropathy; prostate carcinoma; retroperitoneal fibrosis